(untitled) (Bangladesh Rice Journal, 2021)
The damage caused by insect pest is the continual factor for the reduction of rice production. To date, 232 rice insect pest species are identified in Bangladesh and more than 100 species of insects are considered pests in rice production systems globally, but only about 20 - 33 species can cause significant economic loss. The major goal of this study is to explore all the possible ways of developed and proposed technologies for rice insect pests management and minimize economic losses. Insect pests cause 20% average yield loss in Asia where more than 90% of the world’s rice is produced. In Bangladesh, outbreak of several insects such as rice hispa, leafroller, gallmidge, stem borers and brown planthopper (BPH) occurs as severe forms. Based on previous reports, yield loss can reach upto 62% in an outbreak situation due to hispa infestation. However, BPH can cause 44% yield loss in severe infestested field. To overcome the outbreaks in odd years and to keep the loss upto 5%, it is necessary to take some preventive measures such as planting of resistant or tolerant variety, stop insecticide spraying at early establishment of rice, establish early warning and forecasting system, avoid cultivation of susceptible variety and following crop rotation. Subsequent quick management options such as insecticidal treatment for specific insect pest should also be broadcasted through variety of information systems. Advanced genomic tool can be used to develop genetically modified insect and plants for sustainable pest management. In addition, to stipulate farmers not use insecticides at early crop stgae and minimize general annualized loss, some interventions including training rice farmers, regular field monitoring, digitalization in correct insect pests identification and their management (example; BRRI rice doctor mobile app), and demonstration in farmers field. Each technology itself solely or combination of two or more or all the packages can combat the insect pests, save natural enemies, harvest expected yield and contribute to safe food production in Bangladesh. Bangladesh Rice J. 25 (1) : 1-22, 2021